3m+2=6-m

Simple and best practice solution for 3m+2=6-m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+2=6-m equation:



3m+2=6-m
We move all terms to the left:
3m+2-(6-m)=0
We add all the numbers together, and all the variables
3m-(-1m+6)+2=0
We get rid of parentheses
3m+1m-6+2=0
We add all the numbers together, and all the variables
4m-4=0
We move all terms containing m to the left, all other terms to the right
4m=4
m=4/4
m=1

See similar equations:

| 7=x+28/4 | | -7d-4=-4-7d | | -7y+5=-23 | | 4h+6=6+4h | | -10=r/2 | | 4h+6=6 | | 8x+68=9x+78 | | 4-4k=-4k | | 9c=5+9c | | X+37+x+67+180=A | | 6x+3=-4+3x+22 | | -6+2w=2w-1 | | 3x^2+12=7x+32 | | 3r+1=1+3r | | 8x+57=10x+69 | | 6=x-45/5 | | 3(x-3)=0.50(4x-12) | | 3(2b-1)+7=50 | | 23+2x-6=x+16 | | 25t^2+49=0 | | 3(x-3=0.50(4x-12) | | 4u=10u-6u | | 2.3t=1.311 | | 7^a=63 | | (7x+4)^2=5 | | 14n-32=2 | | 8+t=-t | | 7x+61+2x= | | 6.2/2x+1=(7/3)/4 | | x^{2}+10x+2=20x | | -4.3=y/5+8.2 | | 13-a+7=78 |

Equations solver categories